The effects of post activation potentiation warm-up and pre-shot routine programs on driving performance in amateur golfers - Yeemin, W.; Kemarat, S.; Theanthong, A. (PLOS ONE, 2020)
The purpose of this study was to assess the effects of three different programs, i.e. active dynamic warm-up program plus functional resistance warm-up using Theraband plus pre-shot routine program (AFPR); pre-shot routine program (PR); and active dynamic warm-up program plus functional resistance warm-up using Theraband (AF) on driver club head speed, driving distance, and driving accuracy in the amateur golfers. Fifteen amateur golfers with an average age of 19.67 ± 0.89 years and 4.87 ± 1.77 points of average handicap were assigned to participate in either AFPR, PR or AF program. All participants in the three programs practiced three sessions on non-consecutive days per week during the intervention phase. Each participant`s performance was assessed before and after six weeks of the program through hitting ten maximal drives with the ball flight and swing analyzed using the P3ProSwing Golf Simulator and recorded for the driver club head speed, driving distance, and driving accuracy. Multivariate analysis of variance showed no statistically significant differences (P < .05) of the performances of the golfers participated in the 3 programs (club head speed: F = 1.02, P = 0.33; accuracy: F = 0.32, P = 0.72; distance: F = 0.18, P = 0.83). Furthermore, a paired t-tests also showed no statistically significant (P < .05) improvement occurred in the 3 programs after the six-week training. Although the effect of the 3 programs did not show statistically significant increase in the performance of the amateur golfers, however, the three parameters of the performance, i.e. the driver club head speed, the driving distance and the driving accuracy showed certain improvements. The 3 training programs may have benefit to the amateur golfers with certain increases of their performance.